Russia upside down an exit strategy for the second Cold War - Weisberg, Joseph 1965- (PublicAffairs, 2021)
"US sanctions have crippled Russia's economy, and Russia's interventions have exacerbated political problems in America. The old paradigm of America as the free capitalist good guys, fighting Russia, the repressive communist bad guys doesn't apply anymore. Joe Weisberg examines American policy and attempts to understand what Russia truly wants. Russia Upside Down suggests that we are fighting an enemy with whom we have few if any serious conflicts of interest, and our approach is not working. With our own political system in peril and continually buffeted by Russian attacks, Russia Upside Down lays out a new framework for our relationship with Russia at a time when it is badly needed"--
Includes bibliographical references and index
Keywords: Internationale Politik; Russlandbild; USA; United States / Foreign relations / Russia (Federation); Russia (Federation) / Foreign relations / United States; United States / Politics and government / 1989-; Russia (Federation) / Politics and government / 1991-; HISTORY / United States / General; Diplomatic relations; Politics and government; Russia (Federation); United States; Since 1989